Moodle en la educación a distancia - Flores-Piñas, Walter Vladimir; Flores-Piñas, Haydee; Chiri-Saravia, Paulo Cesar; Laura-De La Cruz, Kevin Mario (Puriq, 2022)
The Moodle platform is a software that provides a unique framework within which students can access a wide range of online resources, allowing teachers and students to interact using different communication tools at any time. This platform contains a series of tools that were used during distance education as an educational proposal and in the middle of the 2020 pandemic as a necessity to keep the educational system running. For this reason, this article aims to review the positions of researchers on the benefits of the Moodle platform in distance education. It is concluded that the different researchers have a positive position on the benefits of the Moodle platform in distance education. Other researchers affirmed that during 2020, the use of the platform is a response to the need for continuity of the educational service and not as a proposal to stimulate learning activities.